Hadis Nabi Dalam Politik Kekuasaan: Studi Pemaknaan Hadis Nabi Perspektif Kekuasaan - bin Salman, Abdul Matin (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Hadith of the Prophet in the Politics of Power: Study of the Meaning of the Prophet’s Hadith from the Perspective of Power This article describes the distortion of the Prophet’s traditions by Muslim rulers to achieve their political goals. Politicians find that they can use sensitive issues by distorting the Prophet’s traditions through political meaning. The goal is clear, namely to legitimize the political truth and policies of its rulers, not the truth that Islam brings. Although politicizing the Prophet’s hadiths is a spiritual crime, the ruling religious experts believe that this instrument is the most effective mechanism of exercising social control to gain or maintain power. The method used is descriptive-analytic. This method describes the results of data analysis (political traditions) that have been identified. This method is also supported by theories and concepts related to the theme under study. This technique is used to create a replicative narrative based on valid data, but still pay attention to the context. After conducting studies and analysis, this study finds that the phenomenon of piracy of hadith in politics is not something new. Since the rule of the Umayyads and throughout Arab-Islamic history, religious and ideological theorizations have been described in the form of practical relations between humans, religion, and power. Political fatwas need a prophetic text frame to convince the people. The most effective way to create the principle of loyalty to power is the automation of loyalty to God. On the other hand, disobeying power means disobeying Allah (ka>fir), zindiq, apostates, and even atheists